A microfounded model of money demand under uncertainty, and some empirical evidence - Ingrid Größl; Artur Tarassow (Hamburg University, Department Socioeconomics, 2018)
In this article we derive a microfounded model of money demand under uncertainty built on intertemporally optimizing risk-averse households. Deriving a complete solution of the optimization problem taking the intertemporal budget constraint into account where linearization procedures in our paper take a risky steady state as benchmark. The solution leads to ambiguous effects w.r.t. to the impact of capital market risk as well as inflation risk, which is due to the interplay of substitution and opposing income effects. The econometric results reveal that U.S. households increase their demand for money in response to positive changes in inflation risk and capital market risk, respectively, with both effects lasting permanently.
Keywords: C22; E41; E51; E58; G11; 330; Money Demand; Uncertainty; Inflation Risk; Capital Market Risk; Monetary Policy; Cointegration